English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

e^(ln5)=x . Now express this in log form by thinking of ln(5)
as just an exponent.

lnx=ln5 so obviously

x=5.

2006-11-15 22:44:19 · answer #1 · answered by albert 5 · 0 0

Let's say ln(5) = e to the power of x = 5 here ln(5) = x
Then e to the power of ln(5) = e to the power of x = 5

2006-11-16 06:35:42 · answer #2 · answered by Lucy 1 · 0 0

Let X = e^(ln 5)
Take the ln of both sides.
ln X = ln [e^(ln 5)] = ln 5 * ln e = ln 5 * 1 = ln 5
Take the anti-ln of both sides.
Therefore, x = 5, that is, e^(ln 5) = 5.

2006-11-16 06:36:21 · answer #3 · answered by falzoon 7 · 1 0

Remember the property of logs? It applies here too! That is,

e^(ln x) = x

because e^x and ln(x) are inverses of each other: e^ln x = x, so

e^(ln(5)) = 5

2006-11-16 06:43:05 · answer #4 · answered by Pam 5 · 0 0

fedest.com, questions and answers